Sub-Saharan African Earlier Stone Age Sites along the Atlantic: The Foundations for a New “West Side Story”? - (:unkn) unknown (CCSD, 2023)
International audience
Keywords: African Research; Atlantic Africa; Afrique atlantique; Earlier Stone Age; “west side story”